challenge 25 QUESTION 22 : Quant Question Archive [LOCKED]
Check GMAT Club Decision Tracker for the Latest School Decision Releases http://gmatclub.com/AppTrack

 It is currently 21 Jan 2017, 14:44

### GMAT Club Daily Prep

#### Thank you for using the timer - this advanced tool can estimate your performance and suggest more practice questions. We have subscribed you to Daily Prep Questions via email.

Customized
for You

we will pick new questions that match your level based on your Timer History

Track

every week, we’ll send you an estimated GMAT score based on your performance

Practice
Pays

we will pick new questions that match your level based on your Timer History

# Events & Promotions

###### Events & Promotions in June
Open Detailed Calendar

# challenge 25 QUESTION 22

Author Message
Manager
Joined: 05 Oct 2005
Posts: 200
Followers: 1

Kudos [?]: 7 [0], given: 0

### Show Tags

31 May 2006, 13:37
This topic is locked. If you want to discuss this question please re-post it in the respective forum.

function f (x) SATISFIES f (x) =f (x)^2 FOR ALL x which of the following must be true

f(4) = f(2)*f(2)
f(16) - f(-2) = 0
f(-2) + f(4) = 0
f(3) = 3*f(3)
f(0) = 0

THANKS
_________________

when there is a will there is a way

best regards

VP
Joined: 21 Sep 2003
Posts: 1065
Location: USA
Followers: 3

Kudos [?]: 73 [0], given: 0

### Show Tags

31 May 2006, 14:17
f (x) = f(x^2)
=> f(-2) = f(4) = f(16)
Hence f(-16) = f(-2)
or f(16)-f(-2) = 0.. which is B
_________________

"To dream anything that you want to dream, that is the beauty of the human mind. To do anything that you want to do, that is the strength of the human will. To trust yourself, to test your limits, that is the courage to succeed."

- Bernard Edmonds

Senior Manager
Joined: 15 Mar 2005
Posts: 419
Location: Phoenix
Followers: 2

Kudos [?]: 26 [0], given: 0

### Show Tags

31 May 2006, 14:20
I am not sure if you really meant f(x) = f(x)^2 or f(x) = f(x^2), but I am going with the latter.

1. f(4) = f(2)*f(2)
RHS = f(2)*f(2) = f(2^2)*f(2^2) = f(4)*f(4)
f(4) = f(4)*f(4). Not true.

2. f(16) = f(2).
RHS=f(2) = f(2^2) = f(4) = f(4^2) = f(16) = LHS. True.

3. f(4) = f(-2)
RHS = f(-2) = f((-2)^2) = f(4) = LHS. True.

4. Not true.

5. Not true.
_________________

Who says elephants can't dance?

VP
Joined: 29 Dec 2005
Posts: 1348
Followers: 10

Kudos [?]: 60 [0], given: 0

### Show Tags

31 May 2006, 16:57
kapslock wrote:
3. f(4) = f(-2)
RHS = f(-2) = f((-2)^2) = f(4) = LHS. True.

3. f(-2) + f(4) = 0
f(4) = - f(2)
rhs, = -f(2) = -f(2)^2 = - f(4) .... not true..

but why 5. f(0) = 0 is not true.

LHS = f(0)^2 = f(0).
are 0 and f(0) different?
Manager
Joined: 18 Mar 2004
Posts: 50
Followers: 0

Kudos [?]: 0 [0], given: 0

### Show Tags

03 Apr 2007, 14:36
I understand why B is correct, but why isn't E also correct?

LHS = f(0^2) = f(0)
RHS = 0

0=0 correct.

Thanks
Intern
Joined: 15 Mar 2007
Posts: 16
Followers: 1

Kudos [?]: 13 [0], given: 0

### Show Tags

22 Jul 2007, 05:30
Just wanted to say Hey,

I think we're at the same point in our studies. I've just finished the MGMATs and have taken 2 Challenges.

If you ever need to break down and discuss more of the test. Let me know. . .

MWW7786
Tallahassee, FL
MWW7786   [#permalink] 22 Jul 2007, 05:30
Display posts from previous: Sort by